2018
DOI: 10.1111/1755-5922.12433
|View full text |Cite
|
Sign up to set email alerts
|

Detection of individual responses to clopidogrel: Validation of a novel, rapid analysis using thrombelastography 6s

Abstract: Thrombelastography 6s is a rapid, easy to use and accurate test of ADP-induced clotting using TEG 5000 as a reference. A novel parameter, AUC15, is a viable, time-saving option for this test and has potential value in personalized P2Y12 inhibitor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The most recent TEG ® device that can run the PlateletMapping ® function is the TEG ® 6s. Although most of the data reported in the present study is based on the older TEG ® 5000, readings from the TEG ® 5000 andTEG ® 6s devices have been shown to be well correlated when used in the settings of cardiology (including intra-individual reproducibility) [50], cardiac surgery [51] and trauma [52]. The present review identified several studies from East Asian centers that cited similar performance of thromboelastography to the gold-standard assay (LTA) in terms of identifying HTPR and predicting clinical outcomes, with the largest study identified in this regard [25] showing a strong correlation between thromboelastography and LTA parameters.…”
Section: Discussionmentioning
confidence: 71%
“…The most recent TEG ® device that can run the PlateletMapping ® function is the TEG ® 6s. Although most of the data reported in the present study is based on the older TEG ® 5000, readings from the TEG ® 5000 andTEG ® 6s devices have been shown to be well correlated when used in the settings of cardiology (including intra-individual reproducibility) [50], cardiac surgery [51] and trauma [52]. The present review identified several studies from East Asian centers that cited similar performance of thromboelastography to the gold-standard assay (LTA) in terms of identifying HTPR and predicting clinical outcomes, with the largest study identified in this regard [25] showing a strong correlation between thromboelastography and LTA parameters.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, the TEG 6s device uses a disposable four-channel cartridge to process whole blood samples for assays, and this simplified assay procedure increases the ease of use and substantially reduces the time required for results compared with the TEG 5000 device. 27 28 The TEG 6s device has been tested and validated for the assessment of coagulation dynamics in cardiology patients, 29 trauma patients, 30 and in cardiothoracic surgery, 31 showing high within-device reliability, good diagnostic accuracy, and a close correlation of results with the previous generation TEG 5000 device. 32 With the TEG 6s device, the PlateletMapping assay comes as a single cartridge, containing all necessary components to evaluate the activity of the AA and ADP pathways.…”
Section: The Teg Platelet Mapping Assaymentioning
confidence: 99%
“…A more balanced discussion should mention the 3 recent method validation studies. [12][13][14] It could benefit from including studies in which Plate-letMapping testing compared favorably with other tests. 8,15,16 It could provide more balanced views, including some published in this journal, to the specific issues raised about Plate-letMapping analysis, 11 and it should mention the described potential value of PlateletMapping in various clinical settings.…”
Section: Accuracy and Clinicalmentioning
confidence: 99%